A comprehensive exploration of jatropha curcas biodiesel production as a viable alternative feedstock in the fuel industry – Performance evaluation and feasibility analysis - Jassinnee Milano; Arridina Susan Silitonga; Sieh Kiong Tiong; Mei Yin Ong; Ahmad Masudi; Masjuki Haji Hassan; Taufik Bin Nur; Bela Nurulita; Abdi Hanra Sebayang; Adri Rakha Sebayang (Universitas Muhammadiyah Magelang, 2024)
Jatropha Curcas stands out as a promising plant-based feedstock, offering a non-edible oil that holds great potential as an alternative fuel to traditional diesel. Notably, Jatropha oil boasts favourable fuel properties, including a higher oil content compared to other alternatives. This attribute makes it an attractive candidate for biodiesel production. Importantly, as a non-edible oilseed feedstock, Jatropha Curcas helps mitigate concerns related to food prices and the ongoing food versus fuel debate, offering a sustainable solution to the growing energy demands. Furthermore, the plant exhibits impressive yields, with the potential to produce up to 40% oil weight per seed. This high yield not only enhances the economic viability of Jatropha-based biodiesel but also underscores its efficiency as a feedstock. The discussion extends beyond mere fuel properties, encompassing a comprehensive comparative review that delves into engine performance and emission characteristics associated with Jatropha Curcas. The novelty of this paper lies in its exploration of the crude oil aspects of Jatropha curcas, shedding light on an essential facet often overlooked. By presenting a thorough analysis of fuel properties, engine performance, and emission characteristics, the paper contributes valuable insights to the discourse on sustainable energy solutions. Moreover, it goes beyond technical aspects and provides perspectives on the current economic status, offering a holistic view of the potential impact of Jatropha Curcas in the broader context of renewable energy and economic development.